Numerical comparative study of Nd: YAG solar laser power in end-pumping and sidepumping configurations - MEHELLOU, Saïd; REHOUMA, Ferhat (University of Eloued جامعة الوادي, 2018)
Solar-pumped solid-state lasers are promising for many applications. Since the report of the first sun-pumped solid-state laser, several pumping schemes have been proposed for enhancing the solar laser performance. Although the most efficient laser systems have end-pumping approaches, side-pumping configurations are very suitable for laser power scaling. Here we report numerical comparisons between the performances of Nd: YAG solar lasers by using either end-pumping or side-pumping techniques. In end-pumping configuration, a conical-shaped fused silica light-guide with 3D-CPC output end is used to transmit, compress the concentrated solar radiation from the focal zone of the parabolic mirror into a 4 mm diameter, 30 mm length Nd: YAG rod, within a conical pump cavity, which enables the multi-pass pumping through the laser rod. In side-pumping configuration, a fused silica light-guide with rectangular cross-section is used to collect nearly the same concentrated solar power from the focal zone. The guide also acts as a beam homogenizer by transforming the near-Gaussian profile of the concentrated light spot, incident on its input face, into a uniform rectangular light distribution at its output end. A 2D-CPC cavity is employed in this approach to enhance both the absorbed pump power and distribution along a 4 mm diameter, 30 mm length Nd: YAG rod. Uniform absorption along the rod is achieved, reducing the thermal loading problems. For 900W/m2 solar irradiance, the maximum solar laser power of 60 W is calculated for the end-pumping configuration, corresponding to 40 % enhancement over the collection efficiency of side pumping configuration.
Séminaire National Sur Laser Solaire Et Matériaux ElOeued 5-6 Février 2018
Keywords: Solar irradiance, parabolic mirror, solar-pumped laser, end-pumping, sidepumping, solar laser power.